A review of three-dimensional graphene-based aerogels: Synthesis, structure and application for microwave absorption. (15th April 2021) - Zhi, Dandan; Li, Tian; Li, Jinzhe; Ren, Hesong; Meng, Fanbin
Abstract: Graphene aerogels (GAs) offer a distinctive combination of high porosity, low density, large specific surface area and high compressibility, which make it grab considerable attention in various applications, in particular for high performance electromagnetic wave attenuation. The internal porous structure and three-dimensional (3D) network of GAs solve the phenomenon of graphene sheet layer agglomeration, high conductivity and impedance mismatch in two-dimensional graphene, which is conducive to the improvement of microwave absorption performance. In addition, GAs incorporate other lossy materials as a framework have been widely studied to achieve more efficient microwave absorption. Herein, the latest advances in the synthetic strategies and structural characteristics of graphene-based materials are reviewed. Furthermore, we summarized recent advances in graphene-based aerogels as microwave absorbing materials, including pure GAs and hybrid aerogels with other lossy materials. In addition, we also highlighted the multifunctional microwave absorbing materials. On this basis, we summarized the research status of graphene-based microwave absorbing aerogels and put forward the challenges and outlook of graphene-based microwave absorbing aerogels. Graphical abstract: Image 1 Highlights: The synthetic strategies of graphene-based aerogels are systematically summarized. The structure and microstructure of graphene aerogels are clearly revealed. Recent advances in graphene-based aerogels as microwave absorbing materials are demonstrated. The multifunctional microwave absorbing materials are highlighted. The challenges and prospects of graphene-based microwave absorbing aerogels are put forward.